"Nothing in Nature Is Naturally a Statue": William of Ockham on Artifacts. (7th September 2018) - Zupko, Jack
Among medieval Aristotelians, William of Ockham defends a minimalist account of artifacts, assigning to statues and houses and beds a unity that is merely spatial or locational rather than metaphysical. Thus, in contrast to his predecessors, Thomas Aquinas and Duns Scotus, he denies that artifacts become such by means of an advening 'artificial form' or 'form of the whole' or any change that might tempt us to say that we are dealing with a new thing ( res ). Rather, he understands artifacts as per accidens composites of parts that differ, but not so much that only divine power could unite them, as in the matter and form of a proper substance. For Ockham, artifacts are essentially rearrangements, via human agency, of already existing things, like the clay shaped by a sculptor into a statue or the stick and bristles and string one might fashion into a broom. Ockham does not think that a new thing is thereby created, although his emphasis on the contribution of human artisans seems to leave questions about the ontological status of their agency open. In any case, there are no such things as natural statues, any more than there could be substances created by human artifice.